Ion exchange in wine making with special reference to the hydrogen cycle treatment of white musts - Du Plessis, C. S. (Charl Stegmann) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 1960.